2008
DOI: 10.1021/jp710447j
|View full text |Cite
|
Sign up to set email alerts
|

Nanosize Effects on Hydrogen Storage in Palladium

Abstract: The size dependencies of the hydrogen-storage properties in polymer-coated Pd nanoparticles with diameters of 2.6 ( 0.4 and 7.0 ( 0.9 nm were investigated by a measurement of hydrogen pressure-composition isotherms. Their storage capacities per constituent Pd atom in the particles decreased with decreasing particle size, whereas the hydrogen concentrations in the two kinds of nanoparticles were almost the same and 1.2 times as much, respectively, as that in bulk palladium after counting zero hydrogen occupancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
305
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 354 publications
(335 citation statements)
references
References 58 publications
23
305
2
2
Order By: Relevance
“…Among others, nanoporous palladium is a promising material for catalytic application, 12) hydrogen sensing 13) and hydrogen storage, 14) offering a large surface area. Typical and conventional nanoporous Pd is Pd black, which is composed of coagulated Pd nanoparticles having several hundred nanometer diameters.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, nanoporous palladium is a promising material for catalytic application, 12) hydrogen sensing 13) and hydrogen storage, 14) offering a large surface area. Typical and conventional nanoporous Pd is Pd black, which is composed of coagulated Pd nanoparticles having several hundred nanometer diameters.…”
Section: Introductionmentioning
confidence: 99%
“…Such positive dependency on particle size has been observed experimentally. 10,11) Numbers of hydrogen atoms coordinated by 4-6 metallic atoms are also shown in the figure. In cases of " 2, about 80% of the absorbed hydrogen atoms have six coordinating metallic atoms, which means that they locate mainly at O-sites.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen absorption in nanoparticles has been studied for many years, mainly on Pd. [1][2][3][4][5][6][7][8][9][10][11] Pundt and coworkers 6,7) showed that the crystal structure of hydrogenated Pd nanoparticles varies depending on the cluster size. It includes not only the equilibrium and 0 phases in the f.c.c.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palladium constitutes an ideal model system for hydrogen dissociation and subsequent absorption processes in metals [56][57][58][59]. During catalytic loading, hydrogen molecules are first chemisorbed on the Pd surface, followed by near barrierless dissociation and subsequent diffusion of atomic hydrogen into the lattice.…”
Section: Engineered Nanoparticles and Smart Dustmentioning
confidence: 99%